The exploration of the impact of state ownership on Uganda's New Vision Newspaper's social role - Wasswa, John Baptist (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
The global trends of democratisation and privatisation that swept much of the developing world in the 1980s and 1990s led to significant changes in the conceptualisation, organisation and performance of the media. In Africa democratisation attained a new meaning with associated processes of liberalisation of broadcasting to end the monopoly of broadcasting by the state. The private media of the liberalised market is increasingly putting the public media system, both broadcast and print, under serious competition, and forcing them to adjust to changing circumstances. The New Vision newspaper in Uganda is one such public service media organisations that are owned by the state and yet have to compete in the new more democratic and liberalised environment. This study set out to explore the extent to which state-ownership impacts on The New Vision's social role. Using both qualitative and quantitative methods of date collection, I have established the that although The New Vision is a public service medium for which government remains the major source of news, it does not in most cases give the state more or preferentially prominent coverage at the expense of other interest groups in society. On contrary, basing of the amount of coverage of civil society I established that The New Vision enabled the various groups public sphere to interact. The newspaper to an extent also plays the democratic role of monitoring government although there was little evidence of monitoring of corporate abuse. The nature of The New Vision Statute, and the global trends that have changed the conduct of official and private business, have rendered the theories on the 1980s' development media theories increasingly inapplicable, forcing The New Vision to develop its own version of development journalism that is socially relevant. The study recommends that whereas much of The New Vision Statute is progressive, sections of it should be removed to protect the newspaper from being manipulated by government functionaries, if the it is to continue enabling the public sphere. The newspaper should also increase its monitoring of corporate abuse, and make internal reforms to improve the coverage of development related issues.
Keywords: New Vision (Uganda); Government and the press -- Uganda; Press and politics -- Uganda; Newspaper publishing -- Uganda